2016
DOI: 10.1002/ana.24821
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of super‐refractory status epilepticus with thalamic deep brain stimulation

Abstract: Super-refractory status epilepticus is a condition characterized by recurrence of status epilepticus despite use of deep general anesthesia, and it has high morbidity and mortality rates. We report a case of a 17-year-old boy with a prolonged super-refractory status epilepticus that eventually resolved after commencing deep brain stimulation of the centromedian nucleus of the thalamus. Later attempt to reduce stimulation parameters resulted in immediate relapse of status epilepticus, suggesting a pivotal role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 13 publications
0
49
0
1
Order By: Relevance
“…A recent review of case reports describing use of electro-convulsive therapy to treat RSE/SRSE found electrographic resolution in 6 out of 8 cases, but recovery to baseline in only 2 patients [54]. Isolated reports describe also successful use of anterior thalamic deep-brain stimulation to treat RSE/SRSE [55]. Similar to VNS, the ketogenic diet (KD) has been administered to patients with RSE and SRSE in clinical practice however with fewer cases reported than for VNS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of case reports describing use of electro-convulsive therapy to treat RSE/SRSE found electrographic resolution in 6 out of 8 cases, but recovery to baseline in only 2 patients [54]. Isolated reports describe also successful use of anterior thalamic deep-brain stimulation to treat RSE/SRSE [55]. Similar to VNS, the ketogenic diet (KD) has been administered to patients with RSE and SRSE in clinical practice however with fewer cases reported than for VNS.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in seizure severity is consistent with other studies; stimulation is effective against the most serious seizures, with a concomitant reduction in injuries. (2,4,8,21,22,23,24,25,26,27,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 1067 articles were excluded on the basis of not meeting one or both of these criteria. Results of all 41 studies are summarized in Table 1 1-6, 10-13, 15-17,19,20, 23-25,29-40, 42,44,48, 49, 51-57 and the most frequently studied stimulation targets were the ANT (20 studies 1,5, 11, 15, 16, 19, 25,29,30,32,34,37-40, 48, 49, 53-55 ), the CMT (7 studies 10,11,31,44,[51][52][53], and the HCP (10 studies 3,4,11,12,13,20,33,35,36,56 ). It is noteworthy that some articles evaluated multiple targets and are included more than once.…”
Section: Overall Findingsmentioning
confidence: 99%
“…Seven studies over the past decade have investigated the use of CMT DBS for the treatment of epilepsy in 35 patients. 10,11,31,44,[51][52][53] Treatment response rates range from 50% to 100%, depending on the study and the type of epilepsy being treated. The largest series, published by Son et al in 2016, 44 reported a 79% response rate (11 of 14 patients), with a mean seizure frequency reduction of 68%.…”
Section: Centromedian Nucleus Of the Thalamusmentioning
confidence: 99%
See 1 more Smart Citation